Possibilities of using some qualitative and quantitative methods in a research of a subcultural framing - Kadevich, Vasily Y. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The article deals with the possibilities of using some qualitative and quantitative methods of studying cultural and subcultural framing, which allow to identify, typify and study the cultural frames of various social groups. A consistent combination of the proposed methods, namely, content analysis, linguistic associative experiment, the method of semantic differential and estimated bipolarization, factor analysis and Kruskel – Wallace H-criterion supplemented by a pairwise comparison with the Mann – Whitney U-test, allows us to find optimal resources and opportunities for studying subcultural framing. The application of these methods creates the possibility of an integral interpretation of the results of quantitative and qualitative research.